Serum osteopontin level is independently associated with arterial stiffness in patients on hemodialysis - Po-Yu Huang; Bang-Gee Hsu; Chih-Hsien Wang; Jen-Pi Tsai (Tzu Chi Medical Journal)
Objectives: Carotid–femoral pulse wave velocity (cfPWV) is an approach primarily adopted to define arterial stiffness (AS), which is one of the major contributors to unfavorable cardiovascular outcomes. Osteopontin (OPN), in addition to regulation of bone homeostasis, is an inflammatory mediator of atherosclerosis. We performed a research which estimated the correlation between blood OPN levels and AS in participants on maintenance hemodialysis (MHD). Materials and Methods: One hundred and twenty-six patients who received long-term MHD were included in the cross-sectional study. cfPWV values were calculated based on the carotid and femoral pulsation waveforms. Patients with cfPWV >10 m/s were categorized into the AS group. We utilized a commercially available enzyme-linked immunosorbent assay to check serum concentrations of OPN. Results: Study patients belonging to AS were found to be older, had significantly higher prevalence of underlying diabetes mellitus (DM) and hypertension, had higher systolic blood pressure, and had higher serum total calcium and OPN levels. After adjusting for these variables, multivariate logistic regression analysis disclosed that OPN levels, older age, DM, and total serum calcium levels were independently correlated with AS in patients on MHD. Multivariate analysis based on forward stepwise linear regression also showed that the logarithmically transformed OPN level was an independent correlate of cfPWV in these participants. Conclusion: Serum OPN concentrations had a positive correlation with cfPWV and were therefore related to AS in patients on MHD.